Novel insights into the genetic diversity and clonal structure of natural trembling aspen (Populus tremuloides Michx.) populations: A transcontinental study. (2nd May 2019) - Latutrie, Mathieu; Tóth, Endre Gy.; Bergeron, Yves; Tremblay, Francine
Abstract: Aim: Distribution‐wide trends in climate variability significantly influence the genetic diversity, differentiation and population structure of tree species. This study investigates the effects of disturbances such as fire, fragmentation and climate on modern‐day genetic patterns and clonal structures of trembling aspen at the transcontinental scale. Location: North American boreal zone. Taxon: Trembling aspen ( Populus tremuloides Michx.). Methods: One thousand two hundred individuals in a 30‐site network (40 trees per location) were genotyped with neutral genetic markers and studied in relation to regional differences in climate and surrounding site conditions (aridity, fire cycle, fragmentation). Multiple linear regression models and variance analysis were used to test relationships between genetic indices, structural parameters and the surrounding site factors. Results: Overall, a high percentage of single ramet clones (SRC) and clonal diversity was detected and assumed to be the consequence of multiple sexual reproduction events that took place at all sites, together with suckering, which shapes the clonal structure of populations. Neutral genetic diversity and clonal structure suggested no substantial differences among sites, which were categorized into climate moisture index (CMI) classes; aspen stands across Canada were highly similar from a genetic point of view. Allelic richness (AR) and the average number of alleles ( N a ) varied significantly among clonal organization groups, and landscape fragmentation and a higher frequency of fires showed a negative influence on the levels of genetic diversity. Main conclusions: Our results are inconsistent with the idea that the genotypic diversity of trembling aspen is related to the intensity of disturbance within the boreal forest. It appears that species‐specific disturbance responses and post‐fire recruitment mechanisms are more important than dominant ecological factors, such as climate and fire regimes, in shaping distribution‐wide patterns of neutral genetic variation and clonal structure.